2004
DOI: 10.1124/jpet.103.061796
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization and Cross Talk of α1A- and α1B-Adrenoceptors Coexpressed in Human Embryonic Kidney 293 Cells

Abstract: We established three human embryonic kidney (HEK) 293 cell lines stably expressing ␣ 1 -adrenoceptor (AR) subtypes, one (␣ 1A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…We have found that ␣ 1B -/␣ 1D -AR heterodimers stimulate greater maximal NE responses relative to ␣ 1B -ARs and ␣ 1D -AR expressed alone, suggesting that this heterodimer may act as a high-efficacy complex. This is similar to previous findings on ␣ 1A -/␣ 1B -AR heterodimerization in which NE responses were ϳ10-fold greater in HEK293 cells coexpressing ␣ 1A -and ␣ 1B -ARs (Israilova et al, 2004). In addition, a recent study using ␣ 1 -AR knockout mice found that ␣ 1D -AR and ␣ 1D -/␣ 1B -AR knockout mice had a significant decrease in mean arterial blood pressure, whereas ␣ 1B -AR knockout mice did not, suggesting that ␣ 1D -/␣ 1B -ARs may act cooperatively to regulate blood pressure (Hosoda et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…We have found that ␣ 1B -/␣ 1D -AR heterodimers stimulate greater maximal NE responses relative to ␣ 1B -ARs and ␣ 1D -AR expressed alone, suggesting that this heterodimer may act as a high-efficacy complex. This is similar to previous findings on ␣ 1A -/␣ 1B -AR heterodimerization in which NE responses were ϳ10-fold greater in HEK293 cells coexpressing ␣ 1A -and ␣ 1B -ARs (Israilova et al, 2004). In addition, a recent study using ␣ 1 -AR knockout mice found that ␣ 1D -AR and ␣ 1D -/␣ 1B -AR knockout mice had a significant decrease in mean arterial blood pressure, whereas ␣ 1B -AR knockout mice did not, suggesting that ␣ 1D -/␣ 1B -ARs may act cooperatively to regulate blood pressure (Hosoda et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…Accumulating evidence also indicates that heteromerization might affect signalling pathways regulated by a given protomer. For example, a synergistic increase of the receptor-mediated signalling was observed for the adrenergic a 1A AR-a 1B AR and the muscarinic M 2 R-M 3 R heterodimers (Hornigold et al, 2003;Israilova et al, 2004;Fuxe et al, 2005). On the other hand, G protein signalling might be attenuated upon heteromerization, as has been reported for the opiate MOR-DOR, the a 2A AR-MOR and the adenosinedopamine A 2A R-D 2 R heterodimers (Gomes et al, 2000;Jordan et al, 2003).…”
mentioning
confidence: 77%
“…With respect to the signaling pathway of ␣ 1 -AR, previous studies have suggested that ␣ 1B -AR may control the receptor density and protein expression of ␣ 1A -AR by synergism and/or cross talk of the signaling pathways (16,37). Although it is believed that all ␣ 1 -AR subtypes are coupled to the Gq-protein (42), a study with ␣ 1AB -KO mice suggested the existence of distinct signaling pathways of extracellular signaling-regulated kinase via ␣ 1A -AR and of protein kinase C via ␣ 1B -AR in postnatal cardiac hypertrophy (20).…”
Section: Discussionmentioning
confidence: 99%